Mitochondrial DNA Variation Correlated With the High Altitude Intolerance in Chinese Young Han Males - Li, Zongbin; Liu, Chunwei; Guo, Jun; Shi, Yajun; Li, Yang; Wang, Jinli; Zhou, Shanshan; Chen, Yundai (Frontiers in Cardiovascular Medicine, 2022)
Objective Acute exposure to hypobaric hypoxia can trigger acute mountain sickness (AMS), while the exact mechanism has not been fully revealed. The role of genetic factors in the susceptibility of various high-altitude diseases has also gained much interest. Previous studies have provided evidence for the link between AMS and certain nuclear genes or mitochondrial haplogroup. The correlation between point mutations of mitochondrial DNA (mtDNA) and AMS was further explored in the present study. Methods A total of 84 young Han males residing at low altitude were taken to an elevation of 4,000 m within 40 h. We collected data of their heart rate, blood pressure, peripheral oxygen saturation (SaO2), and obtained blood samples, at sea level and at high altitude. AMS was diagnosed using the revised version of the Lake Louise Questionnaire Score. Sequencing was utilized to identify the association between mtDNA alleles and the occurrence of AMS. We also assessed the association between the presence of AMS and physiological variables, and provided a preliminary discussion of the association between genotypic and phenotypic variation. Results The percentage of neutrophils [Odds ratio (OR): 1.06, 95% confidence interval (CI): 1.01–1.12, P = 0.034) and SaO2 level (OR: 0.87, 95% CI: 0.79–0.95, P = 0.004) were independently associated with the development of AMS. A4576G was a risk factor for AMS (OR: 6.27, 95% CI: 1.2–32.7). T11613C (OR: 0.10, 95% CI: 0.01–0.83), A8923G (OR: 0.15, 95% CI: 0.03–0.76), and T5543C (OR: 0.19, 95% CI: 0.04–0.95) were protective factors for AMS. The level of SaO2 was significantly lower in the individual with A4576G mutation as compared with the individual without A4576G mutation (68.1 ± 7.9 vs. 75.8 ± 6.1, P = 0.001). The level of serum sodium was significantly higher in the individual with A8923G mutation as compared to the individual without A8923G mutation (144.6 ± 1.9 vs. 143.2 ± 1.9, P = 0.027). Conclusions The increase in neutrophils and the disability to preserve oxygen saturation may be associated with the high altitude intolerance in young Chinese Han males. A4576G is the risk factor for AMS. T11613C, A8923G, and T5543C are protective factors for AMS. The role of A8923G mutation may correlate with the sodium and water balance and the role of the A4576G mutation may be related to the disability to maintain blood oxygen level after quickly entering the plateau.